2003
DOI: 10.1074/jbc.m306810200
|View full text |Cite
|
Sign up to set email alerts
|

A Purple-blue Chromoprotein from Goniopora tenuidens Belongs to the DsRed Subfamily of GFP-like Proteins

Abstract: A number of recently cloned chromoproteins homologous to the green fluorescent protein show a substantial bathochromic shift in absorption spectra. Compared with red fluorescent protein from Discosoma sp. (DsRed), mutants of these so-called far-red proteins exhibit a clear red shift in emission spectra as well. Here we report that a far-red chromoprotein from Goniopora tenuidens (gtCP) contains a chromophore of the same chemical structure as DsRed. Denaturation kinetics of both DsRed and gtCP under acidic cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
31
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 20 publications
8
31
0
Order By: Relevance
“…Possibly, a hydration of the N-acylimine C=N bond in the TagRFP chromophore has occurred. Similar hydration of the acylimine bond has been observed for the chromophores in DsRed itself (Gross et al, 2000) and in gtCP (Martynov et al, 2003). In contrast, mTagBFP exhibited a single absorbance maximum at 335 nm in acid, and single maximum at 423 nm in alkali (Figure 3B).…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Possibly, a hydration of the N-acylimine C=N bond in the TagRFP chromophore has occurred. Similar hydration of the acylimine bond has been observed for the chromophores in DsRed itself (Gross et al, 2000) and in gtCP (Martynov et al, 2003). In contrast, mTagBFP exhibited a single absorbance maximum at 335 nm in acid, and single maximum at 423 nm in alkali (Figure 3B).…”
Section: Resultssupporting
confidence: 74%
“…The same fragment was observed upon MS/MS fragmentation of the species ATSFLYGSKTF. Fragments with the same cleavage site near the C=N bond were observed in the case of the N-acylimine-containing chromopeptides derived from proteolysis of DsRed (Gross et al, 2000) and chromoprotein gtCP (Martynov et al, 2003). Therefore, mass-spectral data are consistent with the presence of the acylimine C=N bond and with the absence of the double bond between hydroxyphenyl ring of Tyr64 and imidazole-5-ol ring formed by the Leu63-Tyr64-Gly65 tripeptide.…”
Section: Resultsmentioning
confidence: 68%
“…Positions of molecular mass markers are shown on the Right (sizes in kDa). Upon heating of samples, red fluorescent proteins that carry DsRed-like chromophore often demonstrate partial fragmentation with a break point just before the chromophore (22,23). This well-known effect is also observed for 4D5scFv-KillerRed and results in additional bands corresponding to 31-kDa (4D5scFv with KillerRed C-terminal part) and 24-kDa (KillerRed N-terminal part) fragments.…”
Section: Resultsmentioning
confidence: 90%
“…18 Peptide cleavage has been reported in several fluorescent proteins such as DsRed, gtCP, zFP538, KFP and EosFP. 17,[19][20][21][22][23] The induction of the break is different among the proteins: DsRed and gtCP upon boiling, zFP538 and KFP by autocatalytic process, Kaede and EosFP by UV irradiation. Nienhaus et al 24 recently reported the crystal structure of EosFP in both the green and red forms.…”
Section: Introductionmentioning
confidence: 99%